1989
DOI: 10.1084/jem.169.6.2239
|View full text |Cite
|
Sign up to set email alerts
|

The role of polymorphic I-Ak beta chain residues in presentation of a peptide from myelin basic protein.

Abstract: Proteins encoded by genes in the MHC are highly polymorphic. For class II proteins the highest level of polymorphism is found in distinct regions of variability, notably in the membrane-distal domains. To investigate the role of such residues in antigen presentation, we have tested cells transfected with wild-type or mutant I-Ak beta chains for their ability to present the NH2-terminal peptide of myelin basic protein to a panel of T cell clones. We were unable to detect a gross effect on peptide binding, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Each mutation results in a unique pattern of stimulation of the T-cell clones, and each DR3-restricted T cell clone is stimulated by a different subset of the mutants. This complex relationship of fine structure to antigen-presenting function has been a consistent finding among the murine and human MHC class I and class II molecules examined to date (8,(30)(31)(32)(33)(34)(35)(36)(37) (Table 2). A direct role in antigen presentation for position 74 is consistent with the predicted functional importance of polymorphic residues.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Each mutation results in a unique pattern of stimulation of the T-cell clones, and each DR3-restricted T cell clone is stimulated by a different subset of the mutants. This complex relationship of fine structure to antigen-presenting function has been a consistent finding among the murine and human MHC class I and class II molecules examined to date (8,(30)(31)(32)(33)(34)(35)(36)(37) (Table 2). A direct role in antigen presentation for position 74 is consistent with the predicted functional importance of polymorphic residues.…”
Section: Discussionmentioning
confidence: 88%
“…The essential relationship between the polymorphism of MHC molecules and their function is well documented (4) and suggests that the locations of the hypervariable regions of MHC class II molecules are likely to identify functional domains (5,6). However, only a few studies have examined the particular contribution of individual class II residues to antigen presentation, in murine (7)(8)(9) or human (10) systems.…”
mentioning
confidence: 99%
“…Thus, it has been possible to develop successful immunotherapy of experimental autoimmune encephalitis (3,4) and type II collagen and collagen-induced arthritis. In many of these models, administration of the immunodominant epitope of, for example, myelin basic protein, has been successful in preventing or stopping the progression of neurological symptoms in animals already developing the illness, even after immunization with whole spinal cord emulsified in CFA.…”
Section: Studies In Animal Modelsmentioning
confidence: 99%
“…For the most part, these strategies have attempted to address autoimmune diseases in which the primary pathogenic mechanism and the principal effector mechanism seem to be the result of activated T cells inducing inflammation and damage in a variety of tissues (2). Much of this experimentation has dealt with experimental models of multiple sclerosis (MS) (experimental autoimmune encephalitis) (3,4), rheumatoid arthritis (for which one experimental model is type 2 collagen-induced arthritis), and type 1 diabetes (T1DM) (5), in which the spontaneous disease in nonobese diabetic (NOD) mice is the primary model. Although in antibody-mediated diseases the target of the autoantibodies is frequently well defined, less effort has been directed toward developing specific antigen vaccination to treat the T cells activating these diseases.…”
mentioning
confidence: 99%
“…Exceptions are nifA itself and the reiteratedfix region (10,11). Recent evidence has suggested that in R. meliloti, nifA transcription is controlled primarily by oxygen availability (11).…”
mentioning
confidence: 99%